Analisis Perbaikan Kualitas Produk Besi Beton Ulir dengan Pendekatan DMAIC dan Poka Yoke di PT X - Mochammad Wildani Akbar; Manik Ayu Titisari (JURNAL ILMIAH TEKNIK INDUSTRI DAN INOVASI, 2026)
This study aims to analyse the defect rate of threaded reinforcing bars, identify the dominant defects, determine Six Sigma capability, and design conceptual improvements based on Poka Yoke. The method used is Six Sigma with the DMAIC approach, combined with the Poka Yoke concept, supported by observational data, interviews, and historical data collected over a 15-day period. The results of the study indicate that the production process is not yet stable, with an average value of 3.96 Sigma and a Defects Per Million Opportunities (DPMO) of 6,831.37. A Pareto analysis identified dents (74.25 per cent) and tears (15.60 per cent) as the dominant defects. The FMEA evaluation found that the root cause with the highest priority was the absence of machine initial setup records (RPN 392) and parameter sheets (RPN 343). As a solution, it is proposed to implement Visual and Administrative Poka-Yoke measures via a One-Point Lesson (OPL) board to prevent ‘blind setup’, as well as to make the completion of check sheets mandatory. This proposal is projected to reduce the RPN for tear defects to 128 and for dent defects to 112, which will subsequently be formalised in Standard Operating Procedures (SOPs).